Cover Volume 7, Nomor 3, Juli 2018, Hal. 189 – 301 - Hal. 189 –, Volume 7, Nomor 3, Juli 2018, (Teknik Desain Mekanika; Vol 7 No 3 (2018): juli 2018 : Teknik Desain Mekanika, 2018)
Volume 7, Nomor 3, Juli 2018, Hal. 189 – 301